Ghost ileostomy versus conventional loop ileostomy in patients undergoing low anterior resection for rectal cancer (DRKS00013997): protocol for a randomised controlled trial. Issue 10 (15th October 2020) - Hüttner, Felix J; Probst, Pascal; Mihaljevic, André; Contin, Pietro; Dörr-Harim, Colette; Ulrich, Alexis; Schneider, Martin; Büchler, Markus W; Diener, Markus K; Knebel, Phillip
Abstract : Introduction: Anastomotic leakage is the most important complication in colorectal surgery occurring in up to 20% after low anterior rectal resection. Therefore, a diverting ileostomy is usually created during low anterior resection to protect the anastomosis or rather to diminish the consequences in case of anastomotic leakage. The so-called virtual or ghost ileostomy is a pre-stage ostomy that can be easily exteriorised, if anastomotic leakage is suspected, in order to avoid the severe consequences of anastomotic leakage. On the other hand, an actual ileostomy can be avoided in patients, who do not develop anastomotic leakage. Methods and analysis: The GHOST trial is a randomised controlled pilot trial comparing ghost ileostomy with conventional loop ileostomy in patients undergoing low anterior resection with total mesorectal excision for rectal cancer. After screening for eligibility and obtaining informed consent, a total of 60 adult patients are included in the trial. Patients are intraoperatively randomised to the trial groups in a 1:1 ratio after assuring that none of the intraoperative exclusion criteria are present. The main outcome parameter is the comprehensive complication index as a measure of safety. Further outcomes include specific complications, stoma-related complications, complications of ileostomy closure, frequency of transformation of ghost ileostomy into conventional ileostomy, frequency of terminal ostomy creation, proportion of patients with an ostomy at 6 months after index surgery, anorectal function (Wexner score) and quality of life assessed by the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 and CR29 questionnaires. Follow-up for each individual patient will be 6 months. Ethics and dissemination: The GHOST trial has been approved by the Medical Ethics Committee of Heidelberg University (reference number S-694/2017). If the intervention proves to be safe, loop ileostomy could be spared in a large proportion of patients, thus also avoiding stoma-related complications and a second operation (ileostomy closure) with its inherent complications in these patients. Trial registration number: German Clinical Trials Registry (DRKS00013997); Universal Trial Number: U1111-1208-9742.